The Role of Fiqh Teachers to Improve Students' Learning Motivation and Discipline of Worship through Online Learning During the Covid-19 Pandemic - Layyina, Charisma; Radino, Radino (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – This study aims to explain the role and methods of Fiqh teachers in increasing learning motivation and worship discipline during online learning during the Covid-19 pandemic and the supporting and inhibiting factors. Design/methods/approach – This is a field study using a qualitative, descriptive method. Data were gathered through observation, interviews, and documentation. Data analysis is carried out by reducing data, presenting data, and finally generating conclusions. Findings – The results showed that: 1) The role of the Fiqh teacher in increasing the learning motivation and discipline of worship at MTs N 9 Bantul during online learning was carried out by encouraging students, warm greetings, giving motivation, advice, attention, and Islamic activities so that children carried away in a happy state before undergoing online lessons. Teachers also provide incentives in the form of points, grades, and praise, provide guidance, direct, remind in conducting religious habituation and online learning, as well as evaluating students, and collaborating between schools, teachers, and parents. 2) The inhibiting factors for teachers in implementing their roles are the lack of gadgets, problems with internet data packages, signal networks, lack of assistance and supervision, and student boredom. Research limitation– This study has limitations on the cases observed in MTs N 9 Bantul. Originality/value – The findings of this study provide an overview of how the role of religious teachers in increasing students' learning motivation during the COVID-19 pandemic.